Pengaruh Investasi Pada Industri Kecil dan Industri Menengah Terhadap Penyerapan Tenaga Kerja Di Kota Samarinda - Hadiyanti, Sofia Ulfa Eka (EP FEB UNS, 2015)
Investment as a variable affecting the overall economy, especially in terms of creating job opportunities where expansion of employment opportunities is one of the main problems in development, either in the past or at present. Small and medium industries to survive in times of crisis amid the many industries that have gone bankrupt. Role of Small and Medium Enterprises (SMEs) in the Indonesian economy is basically a big long ago. However, since the economic crisis hit Indonesia, the role of SMEs increased sharply. In addition, the Small and Medium Industries is able to help expand employment and employment opportunities. This study aimed to determine the effect of investments in the industrial sector of small and medium industry sector on employment, and to find investments that are dominant in employment in the city of Samarinda in 2004 until 2008.This research is explanotary (explanation) with a quantitative approach. The data used are secondary data from the value of investments in the sector of Small and Medium Industry, the number of workers absorbed in the sector of Small and Medium Industries is presented in the form of time series. Data were obtained from the Department of Industry and Trade of Samarinda, Samarinda City Department of Labor, and the Central Bureau of Statistics Samarinda. Data were analyzed using multiple linear regression tool that is then reformulated into a simple linear regression estimation model.The analysis shows that investment in the industrial sector of small and medium industrial sector has a significant impact on employment in Samarinda. And after the calculation of partial investment in the secondary industry has a greater impact on employment than small investment in the industrial sector in the city of Samarinda. Keywords: Investment, Small Industries, Medium Industry, EmploymentJEL Classification: J01, L10, L26